Integration of Electrical Properties and Polarization Loss Modulation on Atomic Fe–N-RGO for Boosting Electromagnetic Wave Absorption - Zhang, Kaili; Yan, Yuefeng; Wang, Zhen; Ma, Guansheng; Jia, Dechang; Huang, Xiaoxiao; Zhou, Yu (Nano-Micro Letters, 2024)
Developing effective strategies to regulate graphene's conduction loss and polarization has become a key to expanding its application in the electromagnetic wave absorption (EMWA) field. Based on the unique energy band structure of graphene, regulating its bandgap and electrical properties by introducing heteroatoms is considered a feasible solution. Herein, metal-nitrogen doping reduced graphene oxide (M–N-RGO) was prepared by embedding a series of single metal atoms M–N4 sites (M = Mn, Fe, Co, Ni, Cu, Zn, Nb, Cd, and Sn) in RGO using an N-coordination atom-assisted strategy. These composites had adjustable conductivity and polarization to optimize dielectric loss and impedance matching for efficient EMWA performance. The results showed that the minimum reflection loss (RLmin) of Fe–N-RGO reaches − 74.05 dB (2.0 mm) and the maximum effective absorption bandwidth (EABmax) is 7.05 GHz (1.89 mm) even with a low filler loading of only 1 wt%. Combined with X-ray absorption spectra (XAFS), atomic force microscopy, and density functional theory calculation analysis, the Fe–N4 can be used as the polarization center to increase dipole polarization, interface polarization and defect-induced polarization due to d-p orbital hybridization and structural distortion. Moreover, electron migration within the Fe further leads to conduction loss, thereby synergistically promoting energy attenuation. This study demonstrates the effectiveness of metal-nitrogen doping in regulating the graphene′s dielectric properties, which provides an important basis for further investigation of the loss mechanism. Highlights: 1 Single-atom Fe–N4 sites embedded into graphene were successfully synthesized to exert the dielectric properties of graphene. 2 The absorption mechanisms of metal-nitrogen doping reduced graphene oxide mainly include enhanced dipole polarization, interface polarization, conduction loss and defect-induced polarization. 3 Excellent reflection loss of − 74.05 dB (2.0 mm) and broad effective absorption bandwidth of 7.05 GHz (1.89 mm, with filler loading only 1 wt%) were obtained.